La competencia digital y su importancia en el perfil profesional del comunicador institucional de Machala, 2019 - Caceres Saltos, Fernanda Madeleine (Machala, 2019)
The present research work, case analysis modality, finds its problems in identifying the importance of digital competence in the professional profile of the institutional communicator of the XXI century, a problem that must be analyzed, as an object of study, by professionals and students in communication, which will help to know if what they learn in the classrooms, in matters of institutional communication, is relevant with what is required in the professional exercise in the territory, according to the demands of the Knowledge Society. The general objective of the research is to relate the digital competence with the professional profile of the communicator of public and private institutions in Machala city, year 2019. For this purpose, a case analysis is structured, focused on the professional profile of the communicator of six institutions, an analysis that relies on a qualitative approach methodology, using the triangulation of techniques such as: interview, participatory observation, complemented with the use of the documentary design technique and the bibliographic review, each of them with its respective analysis matrix. It is worth mentioning that at the beginning of the research it was only proposed to analyze the profile of the institutional communicator, but when the research took place, the high protagonism of information and communication technologies (ICT) in the professional exercise of the institutional communicator became evident, which gave a qualitative change to the study, thus incorporating digital competence as an analysis variable. The results show the innovative characteristics that condition the professional profile of the institutional communicator, which are: management of publishing programs for the creation of digital communicational products, management of social networks and writing for the web, without leaving aside the main axis of communication, which is storytelling. In the interviews, there was talk of a connection ecosystem where, thanks to ICTs, new disciplines and specializations have appeared within communication, being this a positive contribution since it positions communication as one of the careers of the future. In this regard, specialists in communication and technology recommend that the communicator should be trained in the digital environment since university classrooms. Among the conclusions, it is evident that institutional communication, as well as technology, is in constant transformation and that is why a continuous training of the institutional communicator in technical-technological subjects is demanded. As for the institutional communication in Machala, the support and commitment of the authorities for the training of their human talent in digital literacy is basic, since the institutional communicators interviewed are predisposed to further develop their digital competence. For this reason, it is recommended that the institutional communicator in the territory incorporate the assiduous practice of technology to overcome the professional challenges that await him in his working life, since these provide unique skills and abilities, which give a differentiated value and competitive advantage to his profile, but the most important thing is that it allows effective, efficient and effective communication with the user of his institutions.
El presente trabajo de titulación, modalidad análisis de caso, encuentra su problemática en identificar la importancia de la competencia digital en el perfil profesional del comunicador institucional del siglo XXI, una problemática que debe ser analizada, como objeto de estudio, por profesionales y estudiantes en comunicación, lo cual ayudará a saber si lo que aprenden en las aulas, en materia de comunicación institucional, es pertinente con lo que se exige en el ejercicio profesional en territorio, acorde a las demandas de la Sociedad del Conocimiento. El objetivo general que envuelve a la investigación es relacionar la competencia digital con el perfil profesional del comunicador de instituciones públicas y privadas en el cantón Machala, año 2019. Para ello se estructura un análisis de caso enfocado en el perfil profesional del comunicador de seis instituciones, análisis que cuenta con una metodología de enfoque cualitativo, usando la triangulación de técnicas como: entrevista, observación participativa, complementado con el uso de la técnica de diseño documental y la revisión bibliográfica, cada una de ellas con su respectiva matriz de análisis. Cabe mencionar que en los inicios de la investigación se planteó únicamente analizar el perfil del comunicador institucional, pero al transcurrir la investigación se evidenció el alto protagonismo de las tecnologías de la información y la comunicación en el ejercicio profesional del comunicador institucional, lo que dio un giro cualitativo al estudio, incorporándose así la competencia digital como variable de análisis. En los resultados se muestran las características innovadoras que condicionan el perfil profesional del comunicador institucional, las cuales son: manejo de programas de edición para la creación de productos comunicacionales digitales, manejo de redes sociales y escritura para la web, sin dejar de lado el eje principal de la comunicación, que es contar historias. En las entrevistas se habló de un ecosistema de conexión donde gracias a las TIC han aparecido nuevas disciplinas y especializaciones dentro de la comunicación, siendo esto un aporte positivo ya que posiciona a la comunicación como una de las carreras del futuro. Al respecto, especialistas en comunicación y tecnología recomiendan que el comunicador debe estar formado en el entorno digital desde los salones universitarios. Entre las conclusiones se evidencia que la comunicación institucional, al igual que la tecnología, está en constante transformación y por ello se demanda una continua formación del comunicador institucional en temas técnico-tecnológicos. En cuanto al escenario de la comunicación institucional en Machala es básico el apoyo y el compromiso de las autoridades por la formación de su talento humano en temas de alfabetización digital ya que existe la predisposición de los comunicadores institucionales entrevistados para desarrollar aún más su competencia digital. Por ello, se recomienda que el comunicador institucional en territorio incorpore la práctica asidua de la tecnología para superar los retos profesionales que le espera en la vida laboral, ya que estas aportan competencias y habilidades únicas, lo que da un valor diferenciado y una ventaja competitiva a su hoja de vida, pero lo más importante es que permite la comunicación eficaz, eficiencia y efectiva con el usuario de sus instituciones.
Keywords: COMPETENCIA DIGITAL; COMUNICACION INSTITUCIONAL; TECNOLOGIA